[Spanish translation] Analysis of Technical and Physical Variables According to the Outcome of the 2018 Russia FIFA World Cup Game - Cabrera Hernandez, Moisés Arturo (2025)
Soccer is the most popular sport in the world, with a growing number of professional players every year. In addition, it is complex and unpredictable with multiple physical, technical, tactical and psychological problems that are critical for performance. In the 90’s, tool-based performance analysis included global positioning systems and optical tracking systems for each player. For this reason, the aim of this study was to analyze physical and technical variables related to the outcome of the game, and the fact that a team qualifies for the different phases of FIFA’s 2018 Russia World Cup. The analysis encompassed all the games played during the 2018 Russia FIFA World Cup—up to 64 games of the 32 participating national teams. A goal score could be insufficient for defining a team’s success, since this variable depends on different and multiple factors. The teams that qualified for the knockout stage showed significantly better performance in some technical variables. On the other hand, regarding physical variables, the most successful teams covered shorter distances with and without the ball, presenting more significant distances in intensity zones 1 and 5 and ball possession. These different aspects are worth analyzing in order to determine their relationship to success in a game.